The impact of child hospitalization on the everyday lives of single parent families - Pamela Camila Fernandes Rumor; Astrid Eggert Boehs (Universidade Federal de Goias, 2013)
This qualitative descriptive study was performed at a pediatric hospitalization unit with the objective to understand the impact of child hospitalization on the daily lives of single parent families. Interviews were conducted with twelve families, represented by the mothers, using a form divided into two parts: construction of the genogram and ecomap and semi-structured questions. Content analysis was used. The results point out that the major factors affecting the everyday lives of single parent families is the dependency on the family support network and the difficulty that both healthcare professionals and institutions have in developing an individualized look at the different family structures when providing their needs. In conclusion, there is a need for thinking and reviewing institutional practices and norms aiming at meeting the true particularities and needs of the everyday lives of today's families. Descriptors: Single-Parent Family; Child, Hospitalized; Family Nursing.